Successful laparoscopic tumorectomy of struma ovarii diagnosed preoperatively - H. Morita; Y. Yamasaki; S. Sugino; H. Koh; N. Kojima; K. Kitajima; T. Yamazaki; K. Takeuchi (IMR Press, 2020)
Introduction: Struma ovarii is rare ovarian tumor. Almost 95% of it is indicated as the benign tumor. Therefore, it is important to be diagnosed preoperatively. A case that is diagnosed successfully as a struma ovarii preoperatively, is presented. Case Report: A 36-year-old Japanese woman G1P1, with no family history nor past history, was referred to this hospital for the treatment of an ovarian tumor, because followed up ovarian tumor gradually became enlarged. Regarding the patient's laboratory data, no tumor marker was elevated. Thyroid function was within normal range. Ultrasound study demonstrated that the tumor was a multilocular mass with solid part. Pelvic MRI indicated stained glass appearance. Although there was a possibility of mucinous malignant tumor as a differential diagnosis, the authors mainly diagnosed it preoperatively as a struma ovarii. Laparoscopic right ovarian tumorectomy was performed and the histological examination revealed as a struma ovarii without malignancy. Conclusions: When the ovarian tumor presents a stainedglass appearance, it is important to diagnose carfeully keeping struma ovarii in mind as a differntial diagnosis.